Granular flow properties of food powders in extrusion processing - McGuire, Cameron (Kansas State University, 2017)
This study relates raw material particulate rheology to the granular flow in a single screw food extruder. Raw materials based on corn (i.e. meal, flour, and starch), wheat (i.e. farina, flour and starch), and sucrose (i.e. granulated, superfine, and powdered) were used as model particulate systems for the study. Various particulate-scale characteristics and flow parameters of these nine materials were determined using a powder rheometer. Properties such as basic flow energy, cohesion, flow function, and effective angle of internal friction were good indicators of flowability in an extruder. Corn meal exhibited lower energy requirements and a higher propensity for flow than corn flour (6.7mJ/g versus 10.7mJ/g, and “free-flowing” versus “cohesive,” according to Flow Function classifications), with wheat farina showing similar results when compared to wheat flour (5.8mJ/g versus 7.9mJ/g, and “highly free-flowing” versus “cohesive”), although both wheat systems showed lower energy requirements than their comparable corn systems. Sugar, being of a different base material and particle shape, behaved differently than these starch-based materials—flow energy decreased and propensity to flow increased as particle size decreased (51.7mJ/g versus 8.0mJ/g, and “free flowing” versus “highly free-flowing”). This large energy requirement for coarse sugar particles was attributed more to particle shape than composition, as the sharp edges of sugar can interlock and restrict movement through the sample. The starch-based results were validated in a particulate flow study involving the above model systems (corn meal, corn flour, wheat farina, and wheat flour) in a pilot-scale single screw extruder. Visualization data, obtained using a transparent plexiglass window during extrusion, confirmed that the flours exhibited higher flow energy requirements and a lower flow factor compared to coarser-particle size during extrusion, seen by the increased peak heights and barrel fill. Additionally, moisture changes were analyzed, showing an increase in energy required for starch-based materials as moisture increases and a decrease in energy for sucrose. Due to the hygroscopic nature of sucrose, moisture was absorbed more rapidly than starch products and the edges of individual particles softened, forming a soft solid. These physiochemical differences resulted in decreased energy requirements for sucrose as moisture was increased (51.7mJ/g to 13.6mJ/g), while corn meal and wheat farina yielded increased energy requirements (6.7mJ/g to 9.1mJ/g and 5.8mJ/g to 9.5mJ/g, respectively). Again, results of starch-based materials were validated using a plexiglass cover during extrusion, clearly showing an increase in barrel fill as moisture content increased for both materials, with corn meal flowing more readily than farina. Lastly, temperature of corn meal and farina was increased to show the difference in behavior of starch-based materials, where farina decreased in energy as temperature increased (14.4mJ/g to 12.1mJ/g ) while corn meal energy requirements increased (12.9mJ/g to 17.2mJ/g). With the results developed from these three experiments, and validated where physically possible, it was concluded that offline powder rheometry is a useful tool for predicting the behavior of food powders. These results were then developed into a computer-simulated model to allow for virtual and visual representation of the conveying action inside an enclosed steel barrel.
Keywords: Extrusion; Processing; Flow; Food powder; Modeling; Rheometry